1993
DOI: 10.1007/bf02796508
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of absorption and scattering properties for various yeast strains by time-resolved spectroscopy

Abstract: An understanding of the optical properties of biological media and cells is essential to the development of noninvasive optical studies of tissues. Unicellular organisms offer a unique opportunity to investigate the factors affecting light propagation, since they can be manipulated in ways impossible for more complex biological samples. In this study, we examined optical absorption and scattering properties of strongly multiple scattering yeast suspensions by means of near-infrared (NIR) time-resolved spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 21 publications
5
31
1
Order By: Relevance
“…3(b,d). It can be seen that both algorithms present similar refractive-index values of the inner cell contents, between 1.34−1.39, coinciding with the expected values for yeast cells [22]. The appearance of vacuoles, containing mostly water, is noticeable.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3(b,d). It can be seen that both algorithms present similar refractive-index values of the inner cell contents, between 1.34−1.39, coinciding with the expected values for yeast cells [22]. The appearance of vacuoles, containing mostly water, is noticeable.…”
Section: Resultssupporting
confidence: 57%
“…We performed TPM of yeast cells (Saccharomyces Cerevisiae, longitudinal diameter range of 5-10 µm), which are eukaryotic organisms that are helpful in noninvasive biological studies [22]. We created two traps near the edges of cells along the y axis, as illustrated in Fig.…”
Section: Datamentioning
confidence: 99%
“…Spectroscopic measurements of light scattering by red blood cells by Steinke and Shepherd, 14 yeast cells by Beauvoit, Chance, and colleagues, 15 and tissue phantoms consisting of suspensions of polystyrene spheres of different size by Mourant, Bigio, and colleagues 16 demonstrated that Mie theory can be used to describe scattering characteristics of those micrometer sized objects.…”
Section: Light Scattering From Cells and Subcellular Structuresmentioning
confidence: 99%
“…10 Previous work has demonstrated that scattering of light by human tissue occurs from both the cells themselves and organelles within the cells, such as the mitochondria and nuclei. 11,12 However, by far the predominate cell type of blood is the erythrocyte or red blood cell (approximately 5ϫ10 6 /L versus 4ϫ10 3 /L for the white blood cell). Because mature erythrocytes contain no nucleus or organelles, it can be hypothesized that the red cell volume is the major source of scattering.…”
mentioning
confidence: 99%